Tradução, adaptação transcultural e validação da Childbirth Self-Efficacy Inventory para uso no Brasil - Bernardo, Elizian Braga Rodrigues (2020)
The aim of the study is to translate, cross-culturally adapt and validate the Childbirth SelfEfficacy Inventory (CBSEI) for use in Brazil. This is a methodological study carried out from February 2019 to December 2019, in six Primary Health Care Units (UAPS) in Fortaleza. Developed in three phases: I - request for authorization from the author of the CBSEI for use in Brazil; II - translation and cross-cultural adaptation, following five steps, initial translation, synthesis of translations, backtranslation, committee of judges and pre-test with the target audience with 30 pregnant women in prenatal care at UAPS Anastácio Magalhães and; a III - regarding the verification of properties with 310 pregnant women who were undergoing prenatal care in the six aforementioned UPAS. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), version 21.0, using the Concordance Index (IVC) tests for the statistical analysis of the judges' responses and the CVI in the pre-test with the 30 pregnant women . Absolute, relative frequencies and measures of central tendency were calculated. The Kolmogorov-Smirnov test was performed in order to identify the normality of the data. The internal structure was measured using Exploratory Factor Analysis (AFE), Kaiser-Meyer-Olkin (KMO) and Bartlett's sphericity. The internal consistency of the CBSEI was obtained by Cronbach's α and total item correlation and criterion validity was obtained with the Wilcoxon Signed Rank test and the Spearman correlation test. The research obtained ethical approval under protocol 11791019.6.0000.80.85. Content validation by the committee of judges showed satisfactory validity indexes, as well as face validation. Most pregnant women were young, with 86.1% (n = 267) up to 35 years of age, median age of 27 years, with a minimum age of 18 and a maximum of 41 years, 54.8% (n = 179 ) had a good education, 82.6% (n = 256) had a partner, 78.7% (n = 244) declared themselves to be non-white, 60% (n = 186) were unemployed and 72.6% (n = 225) had income of up to one minimum wage. As for obstetric and clinical characteristics, it was observed that most pregnant women had a previous history of pregnancy. Of the 310 participating pregnant women, a sample was well divided between those who were in their first pregnancy, 147 (47.4%), and those who were in their second pregnancy or more, 163 (52.6%). Among those with experience of childbirth (n = 150), it was found that the majority, 105 (70%), were primiparous. The final version of the instrument showed Cronbach's α coefficient was> 090 and the Item-Total correlation was> 0.40 in the four sub-scales. Sensitivity tests made it possible to infer that Brazilian pregnant women differentiate between expected results and expected self-efficacy, as well as the active phase and the expulsive period. Having a higher level of education, previous experience with vaginal delivery and feeling confident for normal delivery was statistically associated with higher self-efficacy scores. It was concluded that a reliable, valid and capable instrument to assess maternal self-efficacy in normal birth in the Brazilian context was obtained.